Construction and Application of Patent Valuation Index System--A Case Study of Xuji Group - Bo Feng, Ting Huang, Junwen Feng (Forest Chemicals Review, 1970)
With the continuous progress and development of China's social economy and scientific and technological innovation, intangible assets gradually become more and more important from the psychological viewpoint. The importance of intellectual property rights gradually emerged. Patent right improves the technological innovation ability of enterprises to some extent, promotes the progress of science and technology and the rapid development of economy, and is a precious wealth in the current society. In recent years, the discussion of patent value based on psychological expectation is in full bloom, so people pay more and more attention to the evaluation of patent right. Patent right value can be judged from psychological expectation viewpoints. This paper applies the Analytic Hierarchy Process (AHP) to construct the patent evaluation index system, and find the weight value for each index. Patent evaluation indexes are selected and analyzed. A scientific and systematic patent evaluation index system is constructed, the weight coefficient of each index is calculated based on psychological expectation judgment, and the actual value of patent is estimated by AHP, which provides a new idea for patent evaluation. Finally, take Xuji Group as an example to evaluate its patent value. This paper analyzes and studies the patent value evaluation index system and calculates the specific patent value. A systematic and comprehensive and scientific index system model is constructed, and a case study is analyzed and evaluated by using this model. This study provides a new way of thinking for patent valuation. In addition, it is very necessary to determine the patent technology sharing rate and construct a detailed scientific weight index system.